Severe hyponatraemia with cerebral oedema after Pfizer BNT162b2 mRNA vaccination against COVID-19. (2023) - Dharma, J.F.M.; Montalto, S.; Johnson, D.F.; Chiang, C.; Fourlanos, S.
Abstract: Background: Severe hyponatraemia can lead to serious neurological complications including coma, seizure and death. Hyponatraemia and the Syndrome of Inappropriate Antidiuretic Hormone (SIADH) has been previously described in cases of COVID-19, however there have been few reports post vaccination. We describe a case of severe hyponatraemia post second Pfizer BNT162b2 mRNA vaccination against COVID-19. Case presentation: A 48-year-old previously well woman presented to the emergency department with severe headaches and confusion one day after she received her second Pfizer COVID-19 vaccination. She reported no more than 2.5 L fluid intake. Vital signs were normal. Laboratory investigation revealed serum sodium 113 mmol/L, potassium 3.4 mmol/L, urea 3.5 mmol/L and serum osmolality 266 mmol/kg. TSH, random cortisol and C-reactive protein levels were normal. She was found to be in urinary retention and developed marked polyuria post in dwelling catheter insertion. Following this she underwent spontaneous and rapid correction of serum sodium without intervention. Retrospective analysis showed an inappropriately high copeptin of 4.4 pmol/L. Conclusions: It is important to be cautioned and aware of hyponatraemia as an immediate side effect of COVID-19 vaccination. The exact mechanism is unknown and further research is required to understand the acute endocrine effects which may arise in response to COVID-19 vaccination.